Chronic Traumatic Encephalopathy in Professional American Football Players: Where Are We Now? - Tharmaratnam, Tharmegan; Iskandar, Mina A.; Tabobondung, Tyler C.; Tobbia, Iqdam; Gopee-Ramanan, Prasaanthan; Tabobondung, Taylor A. (Frontiers in Neurology, 2018)
Repetitive head trauma provides a favourable milieu for the onset of inflammatory and neurodegenerative processes. The result of long-lasting head trauma is chronic traumatic encephalopathy (CTE), a disease process well-recognized in boxers, military personnel, and more recently, in American football players. CTE is a chronic neurodegenerative disease with hallmarks of hyperphosphorylated tau (p-tau) aggregates and intercellular lesions of neurofibrillary tangles. The criteria for CTE diagnosis requires at least 1-2 focal perivascular lesions of p-tau in the cerebral cortex, at the depth of the sulci. These pathognomonic lesions aggregate within neurons and glial cells such as astrocytes, and cell processes within the vicinity of small blood vessels. CTE presents in a distinct topographical distribution pattern compared to other tauopathies such as AD and other age-related astrogliopathies. CTE also has an insidious onset, years after repetitive head trauma. The disease course of CTE is characterized by cognitive dysfunction, behavioural changes, and can progress to altered motor function with parkinsonian-like manifestations in later stages. This short review aims to summarize CTE in professional football, epidemiology, diagnosis based on neuroanatomical abnormalities, cognitive degeneration and adverse mental health effects, as well as gaps in the literature and future directions in diagnostics, therapeutics, and preventive measures.